Intravenous Thrombolysis or Medical Management for Minor Strokes - Tu, Wen-Jun; Xu, Yicheng; Liu, Yakun; Li, Jilai; Du, Jichen; Zhao, Jizong (Thrombosis and Haemostasis, 2023)
Objective To evaluate the outcomes of acute ischemic stroke patients with minor deficits treated with either intravenous thrombolysis (IVT) or routine medical management (MM).Methods The study included patients with acute ischemic stroke and National Institutes of Health Stroke Scale (NIHSS) scores of 5 or less who were treated with IVT within 4.5 hours from symptom onset and were classified as the IVT group. The MM group consisted of an equal number of patients with minor strokes, matched for sex, age, and severity, who did not receive thrombolysis. Data on patient information were collected for both groups.Results A total of 26,236 patients were included in this study (13,208 in IVT and 13,208 in MM). Of these patients, 67.9% were men, and the mean age was 67.1 years (standard deviation: 10.9). At 3 months, the IVT group had a higher rate of stroke-independent outcome (Rankin Scale score of 0–2) compared with the MM group (IVT vs. MM: 91.6 vs. 88.6%, absolute difference: 2.5%, 95% confidence interval [CI]: 1.6–3.4%, p = 0.008; adjusted hazard ratio [HR]: 1.2, 95% CI: 1.1–1.4, p = 0.003). Furthermore, there was no significant difference in 3-month mortality rates between the IVT and MM groups (IVT vs. MM: 2.1 vs. 2.5%, absolute difference: −0.6%, 95% CI: −1.1 to 0.3%, p = 0.11; adjusted HR: 0.9, 95% CI: 0.8–1.2, p = 0.09).Conclusion Compared with MM, IVT does not reduce mortality in minor ischemic stroke but improves functional outcomes in minor stroke with an NIHSS score of 3 to 5.
Keywords: ischemic stroke; minor; intravenous thrombolysis; medical management